1983
DOI: 10.1016/0043-1354(83)90263-4
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus and reovirus stability in microorganism-free distilled and wastewaters

Abstract: Abstract--Survival of calf rotavirus and reovirus under controlled laboratory conditions in microorganism-free, distilled and wastewater at 8 and 26°C was examined by periodic measurement of cytopathic effects (CPE) and indirect fluorescent antibody (IFA) assays. Five samples of both water-types were collected and inoculated with the two viruses. Three samples of each type of water were divided into two bottles, one per virus, for incubation at 8°C. Two samples were used at 26°C, one per trial. In the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
12
0
3
Order By: Relevance
“…At present, there is limited information on the fate of viruses in groundwater (20). In our study, poliovirus type 1 was inactivated in groundwater at a somewhat slower rate (-0.13 day-') than (22) for the calf rotavirus seeded in distilled water and wastewater under laboratory conditions in the absence of light. These investigators reported that 7 to 13 days and 80 days were required for a 90%…”
Section: Discussionmentioning
confidence: 60%
“…At present, there is limited information on the fate of viruses in groundwater (20). In our study, poliovirus type 1 was inactivated in groundwater at a somewhat slower rate (-0.13 day-') than (22) for the calf rotavirus seeded in distilled water and wastewater under laboratory conditions in the absence of light. These investigators reported that 7 to 13 days and 80 days were required for a 90%…”
Section: Discussionmentioning
confidence: 60%
“…Metabolic processes increase as temperatures rise and the relationship between population decay and temperature in natural waters has been intensively studied for enteric protozoa [ Naik et al , 1982; deRegnier et al , 1989; Robertson et al , 1992; Medema et al , 1997; Fayer et al , 1998; Walker and Stedinger , 1999; King et al , 2005], bacteria [ Carlucci and Pramer , 1960a; Klock , 1971; Vasconcelos and Swartz , 1976; Mancini , 1978; Gould and Munro , 1981; Lantrip , 1983; Flint , 1987; Evison , 1988; Rhodes and Kator , 1988; Mills et al , 1992; Solic and Krstulovic , 1992; Mezrioui et al , 1995; Sarikaya and Saatchi , 1995; Howell et al , 1996; Nasser and Oman , 1999; Craig et al , 2004] and viruses and phages [ Niemi , 1976; O'Brien and Newman , 1977; McDaniels et al , 1983; Evison , 1988; Nasser and Oman , 1999; Rossi and Aragno , 1999]. As with many biological processes, the most convenient form for the loss rate, when salinity and pH are held constant, is the Arrhenius expression: where T is temperature (°C), = k d is the observed dark death rate at 20°C in fresh water and ϑ M controls the sensitivity of k d to temperature change.…”
Section: Literature Review and Model Developmentmentioning
confidence: 99%
“…McDaniels et al 103 compared the survival of calf rotavirus and reovirus in microorganism-free distilled water and wastewater. In the absence of light and shaking at 26°C, 7 to 13 days were required for a loss of 90% infectivity for both rotavirus and reovirus, while at 8°C, 80 days were required for rotavirus and 260 days for reovirus.…”
Section: H Persistence Of Rotavirus In the Environmentmentioning
confidence: 99%